Design, optimisation and implementation of low-voltage synchronous reluctance motor for solar-powered systems - Boztas, Gullu; Aydogmus, Omur; Caner, Murat; Guldemir, Hanifi (Inst Engineering Technology-Iet, 2019)
Synchronous reluctance motors (SynRMs) are an alternative solution in low-cost applications due to some advantages in terms of manufacturing simplicity. This study deals with a new design and implementation of a SynRM so as to operate at low-voltage level produced by solar panels without using any boost-converter. A 4-inch of standard frame size is chosen for as a submersible pump motor. Preparing for the optimisation step, the commercial design software, Infolytica is used to create the first base structure of the SynRM. As the first step the dc-link voltage, rated current, rated speed, winding layout, slots number, number of the rotor barriers and the outer/inner diameters of the stator are determined. In the next step, the base structure is optimised by using a genetic algorithm (GA) developed in Matlab environment. The developed GA script and finite element analysis software are operated together for optimisation of the rotor geometry. A direct torque control algorithm is used to analyse the performance of the designed motor. The designed motor is also manufactured and tested experimentally.
Keywords: pumps; rotors; torque control; machine control; stators; genetic algorithms; finite element analysis; reluctance motors; rated speed; slots number; outer; inner diameters; base structure; finite element analysis software; low-voltage synchronous reluctance motor; solar-powered systems; synchronous reluctance motors; SynRM; alternative solution; low-cost applications; manufacturing simplicity; low-voltage level; solar panels; boost-converter; standard frame size; submersible pump motor; optimisation step; commercial design software; dc-link voltage; direct torque control algorithm; GA script